BROADCAST NEWS COMMENTARY AS A TOOL FOR SOCIAL CHANGE - Sanusi, Bernice Oluwalanu; Tijani, Abdulraheem Adekilekun (African Journal of Social and Behavioural Sciences, 2024)
This research investigates the role of broadcast news commentary as a catalyst for social change in Nigeria, focusing on its influence on public perception and advocacy efforts. Drawing on a comprehensive review of scholarly literature and empirical evidence, the study examines patterns and dynamics shaping the relationship between commentary and societal transformation. The study utilised a survey research design. The questionnaire was the main instrument of data gathering while 358 respondents were sampled using the convenience sampling technique. Data was then analysed using descriptive statistics. Key findings reveal the significant impact of commentary on shaping public discourse, fostering civic engagement, and mobilizing support for positive change. However, challenges such as bias, sensationalism, and regulatory constraints hinder the effectiveness of commentary as a tool for social change. To address these challenges, the study recommends promoting media literacy, strengthening press freedom, and encouraging diversity in commentary, enhancing professional standards, and fostering collaboration among stakeholders. By implementing these recommendations, stakeholders can harness the transformative power of broadcast news commentary to advance social justice, democracy, and inclusive development in Nigeria.